Unwinding the tangle of adolescent pregnancy and socio-economic functioning: leveraging administrative data from Manitoba, Canada - Aleksandra Jakubowski; Leslie L. Roos; Elizabeth Wall-Wieler (BMC, 2023)
Abstract Background Understanding the relationship between adolescent pregnancy and adult education and employment outcomes is complicated due to the endogeneity of fertility behaviors and socio-economic functioning. Studies exploring adolescent pregnancy have often relied on limited data to measure adolescent pregnancy (i.e. birth during adolescence or self-reports) and lack access to objective measures of school performance during childhood. Methods We use rich administrative data from Manitoba, Canada, to assess women's functioning during childhood (including pre-pregnancy academic performance), fertility behaviors during adolescence (live birth, abortion, pregnancy loss, or no history of pregnancy), and adult outcomes of high school completion and receipt of income assistance. This rich set of covariates allows calculating propensity score weights to help adjust for characteristics possibly predictive of adolescent pregnancy. We also explore which risk factors are associated with the study outcomes. Results We assessed a cohort of 65,732 women, of whom 93.5% had no teen pregnancy, 3.8% had a live birth, 2.6% had abortion, and < 1% had a pregnancy loss. Women with a history of adolescent pregnancy were less likely to complete high school regardless of the outcome of that pregnancy. The probability of dropping out of high school was 7.5% for women with no history of adolescent pregnancy; after adjusting for individual, household, and neighborhood characteristics, the probability of dropping out of high school was 14.2 percentage points (pp) higher (95% CI 12.0-16.5) for women with live birth, 7.6 pp. higher (95% CI 1.5-13.7) for women with a pregnancy loss, and 6.9 pp. higher (95% CI 5.2-8.6) for women who had abortion. They key risk factors for never completing high school are poor or average school performance in 9th grade. Women who had a live births during adolescence were much more likely to receive income assistance than any other group in the sample. Aside from poor school performance, growing up in poor households and in poor neighborhoods were also highly predictive of receiving income assistance during adulthood. Discussion The administrative data used in this study enabled us to assess the relationship between adolescent pregnancy and adult outcomes after controlling for a rich set of individual-, household-, and neighborhood-level characteristics. Adolescent pregnancy was associated with higher risk of never completing high school regardless of the pregnancy outcome. Receipt of income assistance was significantly higher for women having a live birth, but only marginally higher for those who had a pregnancy that ended in loss or termination, underlining the harsh economic consequences of caring for a child as a young mother. Our data suggest that interventions targeting young women with poor or average school marks may be especially effective public policy priorities.